Birds of a Feather or Fish Out of Water? Policewomen Taking Rape Reports. (April 2014) - Rich, Karen; Seffrin, Patrick
Police departments and victim advocacy organizations are gendered institutions. In addition, rape is a gendered crime with most victims being female and most perpetrators male. On the job, female officers may experience harassment, discrimination, and pressure to conform. Rape cases may present unique challenges for them given these dynamics. A total of 429 police officers were quantitatively surveyed on colleagues' comments about rape victims, utilization of victim advocates, perceptions of rape-related training, and inclination to encourage loved ones to make reports. Significant gender differences were identified in most areas. Results are discussed in relation to previous research on gender and police work.